RHYTHM SYLLABLE BASED ON 3N KI HADJAR DEWANTARA IN LEARNING RHYTHMICS FOR PRIMARY SCHOOL TEACHERS - Permana, Faisal Rahmat (Cirebon International Conference on Education and Economics Proceeding, 2024)
This research develops a rhythmic learning method based on Rhythm Syllable with the 3N (Niteni, Nirokke, Nambahi) approach from Ki Hadjar Dewantara, using Design-Based Research (DBR). This method aims to improve elementary school teachers' rhythmic skills through rhythmic syllables that are easy to remember and apply. The research was conducted using a qualitative approach in an elementary school teacher education program, collecting data through observation, interviews and documentation. The results show that 3N-based Syllable Rhythm is effective in improving rhythmic understanding and skills. The use of rhythmic syllables helps teachers better recognize and reproduce rhythmic patterns, while the 3N concept encourages active participation in learning. Rhythmic learning has various benefits, including improving motor skills, concentration and creativity. This approach provides significant benefits in rhythmic teaching and can be applied in music education to improve elementary school teachers' rhythmic skills, in accordance with Ki Hadjar Dewantara's educational philosophy which emphasizes freedom and creativity in learning.